How do you differentiate #f(x)=x/(x-1)^2+x^2-4/(1-1x)# using the sum rule?

Answer 1

#f'(x)=(2x)/(x-1)^3+(x-1)^2+2x-4/(1-x)^2#

#"differentiate using the "color(blue)"chain/product rules"#
#"given "y=f(g(x))"then"#
#dy/dx=f'(g(x))xxg'(x)larrcolor(blue)"chain rule"#
#"given "y=g(x)h(x)" then"#
#dy/dx=g(x)h'(x)+h(x)g'(x)larrcolor(blue)"product rule"#
#"differentiate "x/(x-1)^2" using chain/product rules"#
#x/(x-1)^2=x(x-1)^-2#
#d/dx(x(x-1)^2)#
#=x(-2(x-1)^-3)+(x-1)^2#
#=-2x(x-1)^-3+(x-1)^2=(2x)/(x-1)^3+(x-1)^2#
#"differentiate "4/(1-x)" using the chain rule"#
#4/(1-x)=4(1-x)^-1#
#d/dx(4(1-x)^-1)=-4(1-x)^-2(-1)=4/(1-x)^2#
#"returning to the original question"#
#f'(x)=(2x)/(x-1)^3+(x-1)^2+2x-4/(1-x)^2#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To differentiate ( f(x) = \frac{x}{(x - 1)^2} + \frac{x^2 - 4}{1 - x} ) using the sum rule:

  1. Differentiate each term separately.
  2. Apply the sum rule to combine the derivatives.

Given ( f(x) = \frac{x}{(x - 1)^2} + \frac{x^2 - 4}{1 - x} ), let's differentiate each term:

For the first term, ( \frac{x}{(x - 1)^2} ):

  • Apply the quotient rule.
  • ( u = x ) and ( v = (x - 1)^2 ).
  • Differentiate ( u ) and ( v ) separately.

[ \frac{d}{dx} \left( \frac{x}{(x - 1)^2} \right) = \frac{u'v - uv'}{v^2} ]

For the second term, ( \frac{x^2 - 4}{1 - x} ):

  • Apply the quotient rule.
  • ( u = x^2 - 4 ) and ( v = 1 - x ).
  • Differentiate ( u ) and ( v ) separately.

[ \frac{d}{dx} \left( \frac{x^2 - 4}{1 - x} \right) = \frac{u'v - uv'}{v^2} ]

Once you have the derivatives of each term, apply the sum rule:

[ f'(x) = \frac{d}{dx} \left( \frac{x}{(x - 1)^2} \right) + \frac{d}{dx} \left( \frac{x^2 - 4}{1 - x} \right) ]

Finally, simplify the resulting expression to obtain ( f'(x) ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7